Self-supported cuprous oxide/graphdiyne nanosheets array for efficient ammonia synthesis - Jiayu Yan; Fanle Bu; Lu Qi; Shuya Zhao; Zhaoyang Chen; Yurui Xue (ChemPhysMater)
Electrocatalytic reduction of nitrates plays a crucial role in ammonia (NH3) production. In this study, a novel cuprous oxide/graphdiyne (Cu2O/GDY) electrocatalyst was synthesized by growing Cu2O/GDY on a Cu substrate with a porous architecture capable of increasing the number of active sites and enhancing mass transfer ability. The sp-C–Cu bonds between Cu2O and GDY facilitate rapid charge transfer and promote direct electron transport from active sites to reaction intermediates. Consequently, the electrocatalyst exhibits high NH3 production performance with a yield rate (YNH3) of 652.82 µmol h−1 cm−2 and Faradaic efficiency of 82.98% at −1.8 V (vs. SCE) under ambient conditions in an aqueous solution. This work introduces a novel and efficient approach for the in situ fabrication of self-supported heterostructures, thereby enabling high-performance ammonia production under ambient conditions.